2010
DOI: 10.5539/elt.v3n1p128
|View full text |Cite
|
Sign up to set email alerts
|

The Motivation of L2 Learners: Does it decrease with age?

Abstract: This study investigated the motivation of a heterogeneous group of students studying English as a foreign language at the International School in Tripoli area. The aim of the study was to find out the extent to which various factors affect students' motivation and achievement in second/foreign language learning particularly as they enter the senior high school. The research also looked into the temporal dimension of L2 motivation to see if the students' motivation changes as they enter the senior high school. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 21 publications
(11 reference statements)
8
39
0
Order By: Relevance
“…The research also highlighted that the motivational level reduces due to lack of required context and due to lack of exposure to native-English speaking people (Ghenggesh, 2010).…”
Section: Attitude and Motivation Of Students Towards Learning Englishmentioning
confidence: 99%
See 1 more Smart Citation
“…The research also highlighted that the motivational level reduces due to lack of required context and due to lack of exposure to native-English speaking people (Ghenggesh, 2010).…”
Section: Attitude and Motivation Of Students Towards Learning Englishmentioning
confidence: 99%
“…Ghenghesh carried out a research in Tripoli areas International school where students learn English as second language to assess the factors, which influence the motivational level of the students towards learning the language (Ghenggesh, 2010). The research has a mixed research approach wherein the interviews of teachers were carried out and students were surveyed.…”
Section: Relevant Past Studiesmentioning
confidence: 99%
“…Many studies point to a decrease of motivation with age (Chambers 1999;Williams, Burden and Lanvers 2002;Cenoz 2003;Ghenghesh 2010). Tragant (2006) found that secondary education students were more motivated than primary education students, but this tendency stops somewhere in upper secondary education.…”
Section: Motivation and Other Factors: Age And Type Of Instructionmentioning
confidence: 99%
“…As suggested by many L2 researchers, L2 motivation, a major learner factor, is signifiantly influenced by social and contextual factors (Dörnyei, 2001;Ghenghesh, 2010;Long, Ming, & Chen, 2013;Kim, 2010;Kormos, Kiddle, & Csizér, 2011;Noels, Pelletier, & Vallerand, 2000;Vandergrift, 2005;Zhao, 2012). Regarding the close interaction between an external context and L2 learners' internal responses to the context, Ryan (1985, 1995) proposed self-determination theory which explicates two main motivational orientations: intrinsic and extrinsic ones.…”
Section: Introductionmentioning
confidence: 99%
“…Learners may also be extrinsically motivated to learn a language because of some potential rewards that can be gained by developing language competence. L2 researchers have applied this self-determination theory to different contexts under a variety of social influences and have revealed that an L2 learner's response to the context forms a certain motivational orientation, which is significantly related with learner autonomy (Dörnyei, 2001;Ghenghesh, 2010;Long, Ming, & Chen, 2013;Kormos, Kiddle, & Csizér, 2011;Noels et al, 2000;Vandergrift, 2005).…”
Section: Introductionmentioning
confidence: 99%